As boys become men - Mukul Kumar (New Delhi, 2016)
Freedom, friends and fun. That$1 (Bs how most of us remember our college years. But for those studying to get into the coveted Indian Civil Services, college life acquires an additional layer. As Boys Become Men revolves around three such boys, Mihir, Uday and Sandeep, who set out together to crack the Civil Services exam. Narrated by the thoughtful and intense Mihir, this book explores college life, friendship, romance, leaving home and adjusting to a new environment, and describes how negotiating the path between dharma and desire, love and lust, can be tricky.s
Keywords: Fiction - English